ER stress and Rho kinase activation underlie the vasculopathy of CADASIL - Neves, Karla B. (JCI Insight, 2019)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) leads to premature stroke and vascular dementia. Mechanism-specific therapies for this aggressive cerebral small vessel disease are lacking. CADASIL is caused by NOTCH3 mutations that influence vascular smooth muscle cell (VSMC) function through unknown processes. We investigated molecular mechanisms underlying the vasculopathy in CADASIL focusing on endoplasmic reticulum (ER) stress and RhoA/Rho kinase (ROCK). Peripheral small arteries and VSMCs were isolated from gluteal biopsies of CADASIL patients and mesentery of TgNotch3(R169C) mice (CADASIL model). CADASIL vessels exhibited impaired vasorelaxation, blunted vasoconstriction, and hypertrophic remodeling. Expression of NOTCH3 and ER stress target genes was amplified and ER stress response, Rho kinase activity, superoxide production, and cytoskeleton-associated protein phosphorylation were increased in CADASIL, processes associated with Nox5 upregulation. Aberrant vascular responses and signaling in CADASIL were ameliorated by inhibitors of Notch3 (γ-secretase inhibitor), Nox5 (mellitin), ER stress (4-phenylbutyric acid), and ROCK (fasudil). Observations in human CADASIL were recapitulated in TgNotch3(R169C) mice. These findings indicate that vascular dysfunction in CADASIL involves ER stress/ROCK interplay driven by Notch3-induced Nox5 activation and that NOTCH3 mutation–associated vascular pathology, typical in cerebral vessels, also manifests peripherally. We define Notch3-Nox5/ER stress/ROCK signaling as a putative mechanism-specific target and suggest that peripheral artery responses may be an accessible biomarker in CADASIL.